Analysis Of Retail Sector Market Reaction In Indonesia On Social Media And Investor Sentiment - Khaerunnisa Nur Fatimah Syahnur; Dewi Fatmarani Surianto; Muhammad Try Dharsana (Jurnal Manajemen Bisnis, 2023)
This study aims to examine the effect of social media and investor sentiment on the market reaction of the retail sector in Indonesia. Content analysis determines investor sentiment obtained from social media. Information related to the 2019 Indonesian presidential election was used for content analysis. The study results provide evidence that the information available on social media and online investor sentiment have a positive effect on the market reaction of the retail sector in Indonesia. This study also supports the use of signal theory to explain the effect of information available on social media on the capital market in Indonesia.